Does Economic Growth Efficient and Environmental Safety? The Case of Transportation Sector in Indonesia - Priyagus, Priyagus (International Journal of Energy Economics and Policy, 2021)
Business challenges in the transportation sector in Indonesia will be tough if they are only profit-oriented, without considering environmental aspects. A vital phenomenon that also motivated the author to investigate the Environmental Kuznets Curve (EKC) hypothesis for the transportation sector in Indonesia for the period 2000-2019. We applied the analysis model using Partial Adjustment Model (PAM) with control variable (labor) and without control variable based on Least Square (LS) and Robust Least Square (RSL).This finding detects that it significantly proved the EKC hypothesis in the transportation sector for the estimation of emissions with short-term control variables. In energy estimation, the result is not significant. Economic activity and energy consumption in the transportation sector play an inefficient role in supporting GHG emissions because the actual maximum value of economic activity is still on the left or before it reached the maximum EKC value. The government must be consistent with regulations, cooperate between institutions, and require continuous public attention. This is certainly useful for encouraging investment and achieving more efficient economic growth by maintaining a quality environment in the long term. Keywords: Environmental Kuznet Curve, Partial Adjustment Model, Least Square, Robust Least Square, transportation sector, carbon emissions, Indonesia. JEL Classifications: F18, C24, C12, L91, F64. DOI: https://doi.org/10.32479/ijeep.11807